Contribuições da Pesquisa Sócio-Histórica para a Compreensão dos Contextos Interacionais da Sala de Aula de Línguas: Foco na Formação de Professores - Magalhães, Maria Cecília Camargo (The ESPecialist, 2012)
This paper discusses classroom interaction as socially and culturally situated, based on the theoretical framework provided by (a) socio-cultural and historical research (Vygotsky and his followers); and (b) the research on the poliphonic and dialogue nature of classroom discourse (Bakhtin/ Voloshinov and his followers). It aims at rethinking the discussion of the processes of knowledge negotiation in the language classroom and the quality of student learning based on a socio-historical frame and its crucial importance for teacher development.